APPLICATION OF VALUE ENGINEERING IN ARCHITECTURAL WORK ON THE LAHAIROI LATERI CHURCH, AMBON CITY - Irfanto, Ryobi (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
Effective construction cost control such as saving construction costs will increase the chances of project success and user satisfaction. The biggest component in construction costs is material. High material costs necessitate a review of building functions. Construction savings are made by reviewing the largest cost components in architectural work. Review of material components is carried out using the value engineering method. Value engineering is a method for getting an alternative picture so that the costs incurred are more efficient than the initial planning costs. The application of value engineering to construction projects has a major impact on planning by generating reviews to obtain cost effectiveness. Research was conducted at the Lahairoi Lateri Church Building project located in Ambon City. The aim of this research is to find alternative material substitutes for architectural work and obtain total cost savings by using the concept of value engineering. The use of the value engineering concept is carried out by information phase, analyzing the function of using index function analysis techniques, identifying alternative materials, and evaluating the results of the alternative materials. Research using the value engineering concept on the Lahairoi Lateri Church Building Construction project, Ambon City achieved cost savings of 861,116,841.05 IDR. This amount saves 5.32% of the initial architectural work costs of 16,170,539,500 IDR. These results show that value engineering can eliminate unnecessary costs in church-type building without changing the building function.